KINERJA PENYULUH PERTANIAN KABUPATEN KULON PROGO, GUNUNGKIDUL, SLEMAN DAN BANTUL DI ERA OTONAMI DAERAH (THE PERFORMANCE OF AGRICULTURE EXTENSION WORKERS (AEWS) IN KULON PROGO, GUNUNGKIDUL, SLEMAN AND BANTUL REGENCIES IN ERA OF REGIONAL AUTONOMY) - Istiningsih, Istiningsih (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2008)
This research is a comparative study. The result showed that the performance of the AEWs in Kulon Progo, Gunungkidul, and Bantul Regencies generally are in a sufficient category, that while that those in Sleman regency is in a low category. The result of the major hypothesis testing showed that there is a significant difference in the performance of the AEWs in the four regencies. The result of the minor ypothesis testing showed there are significant differences in the performance of the AEWs in the four regencies based on their role as education servant, motivator of farm business, agriculture consultants, and as farmers counterparts, knowledge, attitude, and skill as AEWs. The other important results of this research are that the AEWs in Bantul and Kulon Progo have higher performance than the AEWs in Gunungkidul.